2020
DOI: 10.3390/f11030268
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Site-Specific Conditions on Estimation of Forest above Ground Biomass from Airborne Laser Scanning

Abstract: Forest aboveground biomass (AGB) is an important variable in assessing carbon stock or ecosystem functioning, as well as for forest management. Among methods of forest AGB estimation laser scanning attracts attention because it allows for detailed measurements of forest structure. Here we evaluated variables that influence forest AGB estimation from airborne laser scanning (ALS), specifically characteristics of ALS inputs and of a derived canopy height model (CHM), and role of allometric equations (local vs. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In this study, three tree stands were selected in the LYS catchment (LYS 1K, LYS 2K, and LYS 4K) and three stands in the PLB catchment (PLB 2K, PLB 3K, and PLB 5K), these stands were the object of previous long-term research, thus the soil conditions were known as well as tree height information, which was measured in-situ and modelled using the LiDAR data [62].…”
Section: In-situ Ground Truthmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, three tree stands were selected in the LYS catchment (LYS 1K, LYS 2K, and LYS 4K) and three stands in the PLB catchment (PLB 2K, PLB 3K, and PLB 5K), these stands were the object of previous long-term research, thus the soil conditions were known as well as tree height information, which was measured in-situ and modelled using the LiDAR data [62].…”
Section: In-situ Ground Truthmentioning
confidence: 99%
“…The tree characteristics-height, crown, and top-derived from the CHM raster (Figure 7) were compared with the in-situ measurements that were collected in 2015 [62]. Table 6 summarizes the evaluation statistics.…”
Section: Uav Tree Height Crown and Top Detectionmentioning
confidence: 99%
“…In the field it was observed that tree cuts were common in this particular forest stand. It will be interesting to test in the future, if this approach can be further employed or adjusted for estimating the forest aboveground biomass in a similar way as airborne laser scanning has been employed [45].…”
Section: Discussionmentioning
confidence: 99%
“…In this study three tree stands were selected in the LYS catchment (LYS 1K, LYS 2K, LYS 4K) and three stands in the PLB catchment (PLB 2K, PLB 3K, PLB 5K), these stands were the object of previous long-term research, thus the soil conditions were known as well as tree height information which was measured in-situ and modelled using the LiDAR data [45].…”
Section: In-situ Ground Truthmentioning
confidence: 99%
See 1 more Smart Citation